2021
DOI: 10.3389/fimmu.2021.761345
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinated Histone H3 Mediates Sepsis-Induced Lung Injury Through Activating Caspase-1 Dependent Inflammasome Pathway

Abstract: Sepsis is a life-threatening organ dysfunction caused by dysregulated host response to infection that often results in acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). An emerging mechanism of sepsis-induced ARDS involves neutrophils/macrophages undergoing cell death, releasing nuclear histones to cause tissue damage that exacerbates pulmonary injury. While published studies focus on unmodified histones, little is known about the role of citrullinated histone H3 (CitH3) in the pathogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…This has also been demonstrated in patients with sepsis since a correlation between high serum CitH3 and poor prognosis of sepsis is elucidated [61][62][63]. Novel research into systemic dysfunction in sepsis also identified a higher circulating CitH3 level in serum [64][65][66]. Tian et al implicated that elevated CitH3 is correlated with sepsisinduced acute respiratory distress syndrome and lung dysfunction in patients.…”
Section: Citrullinationmentioning
confidence: 91%
See 1 more Smart Citation
“…This has also been demonstrated in patients with sepsis since a correlation between high serum CitH3 and poor prognosis of sepsis is elucidated [61][62][63]. Novel research into systemic dysfunction in sepsis also identified a higher circulating CitH3 level in serum [64][65][66]. Tian et al implicated that elevated CitH3 is correlated with sepsisinduced acute respiratory distress syndrome and lung dysfunction in patients.…”
Section: Citrullinationmentioning
confidence: 91%
“…Tian et al implicated that elevated CitH3 is correlated with sepsis-induced acute respiratory distress syndrome and lung dysfunction in patients. In mechanism, CitH3 activates caspase-1-dependent inflammasome in bone marrow-derived macrophages and bone marrow-derived dendritic cells and induces acute lung injury (ALI) [ 65 ].…”
Section: Histone Modifications In Sepsismentioning
confidence: 99%
“…Hematoxylin and eosin were subsequently used to stain the sections, 16 followed by visualization under a light microscope at 200× magnification. The severity of ALI was scored as previously described, 17 with the assessment of neutrophils and alveolar macrophages, septal hemorrhage and congestion, septal mononuclear cells/lymphocytes infiltration, alveolar hemorrhage and edema.…”
Section: Methodsmentioning
confidence: 99%
“…Citrullinated histone H3 (CitH3) is a biomarker for NETs formation, a recent study indicated that it promoted ARDS in sepsis via regulating caspase-1-dependent inflammasome pathway . OLFM4 exacerbated lung epithelial cells dysfunction in ARDS induced by sepsis via mediating signaling transduction of NF-κB, which accelerates the assembly of NLRP3/ASC/caspase-1 .…”
Section: Small-molecule Compounds From Dietary Plants Alleviate Sepsi...mentioning
confidence: 99%